Prevalence of pilus islets and association with clonal complex in Streptococcus pneumoniae isolated from children in Suzhou, China - Jiaming Shen; Xiaofei Liu; Lili Huang; Youyi Zhang; Yunzhen Tao; Mengzhen Wang; Genming Zhao; Xuejun Shao; Tao Zhang (Microbiology Spectrum)
ABSTRACT Pilus islets (PIs) in Streptococcus pneumoniae play a crucial role in bacterial adhesion and virulence. This study aims to investigate the prevalence of PIs and explore their associations with serotypes, clones, and antibiotic susceptibility in S. pneumoniae isolated from children in Suzhou, China. A total of 341 S. pneumoniae isolates from aseptic specimens, ear secretions, and sputum between 2018 and 2021 were analyzed. Serotyping was conducted using latex and Quellung reactions. Antimicrobial susceptibility testing was performed using E-test methods. Multi-locus sequence typing (MLST) was conducted to identify the sequence types and clonal complex (CC). PI-1 and PI-2 were detected by PCR assays for the rlrA and sipA genes, respectively. A total of 63.6% of the included S. pneumoniae isolates expressed at least one type of PI, with strains of PCV13 vaccine serotypes showing a significantly higher positive rate of PIs than non-vaccine serotype strains (71.6% vs. 24.5%). PI prevalence varied across sample sources and clonal complexes. While a stronger association of PIs with clones than with serotypes was identified, most of the piliated isolates belonged to prevalent CCs, such as CC271. In addition, piliated isolates tended to be resistant to antibiotics compared to the non-piliated isolates. Our study highlights the high prevalence of PIs and the implications on antibiotic resistance and clonal dissemination of S. pneumoniae among children in Suzhou, China.IMPORTANCEThis study reveals a high prevalence of PIs in Streptococcus pneumoniae among children in China, which differs from isolates in other countries and highlights their implications for antibiotic resistance and clonal dissemination. To our knowledge, we are the first to report PI prevalence across different clinical samples within the same population, suggesting a potential link between PIs and acute otitis media (AOM) in Chinese children. These findings contribute valuable insights into the role of PIs in clinical settings and underline the need for targeted interventions, including vaccine strategies and antimicrobial stewardship protocols. By advancing our knowledge of PI epidemiology, this research enriches the existing literature and aims to inform public health initiatives, ultimately improving health outcomes for vulnerable pediatric populations.